Hepatocellular carcinoma - Kidi, Mehmet Mutlu (Scientific Reports in Medicine, 2024)
Hepatocellular carcinoma (HCC) is a primary liver cancer predominantly arising in individuals with chronic liver diseases such as cirrhosis or chronic hepatitis B virus (HBV) infection. Accounting for approximately 75% of primary liver tumors, HCC’s global epidemiology is significantly influenced by HBV and hepatitis C virus (HCV) infections, alcohol and tobacco use, metabolic syndrome, diabetes, obesity, and aflatoxin B1 exposure. Preventive measures, including HBV vaccination and direct-acting antivirals for HCV, have reduced incidence rates, particularly in younger populations. Early diagnosis through surveillance in high-risk groups is critical, employing imaging modalities like ultrasound, CT, and MRI, alongside biomarkers such as alpha-fetoprotein (AFP). Prognostic assessments utilize scores like Child-Pugh and ALBI. Treatment strategies for HCC are multifaceted, involving surgical resection, locoregional therapies (e.g., transarterial chemoembolization), and systemic therapies, including targeted and immunotherapies. Despite advancements, treatment efficacy remains a challenge, necessitating ongoing research into novel therapeutic approaches and predictive biomarkers to enhance personalized treatment and improve outcomes for HCC patients.